Researching The Reference Points Of Therapeutic Work In The Birštonas School Of Existential Therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
The paper introduces the reference points of therapeutic work in the Birštonas School of existential therapy. The results of the qualitative research using thematic analysis are three main themes: dimension of therapeutic relationship, dimension of therapeutic interaction, dimension of theoretical understanding of therapy. Sixteen sub-themes unfold these three dimensions.
Keywords: Qualitative research; therapeutic relationship; therapeutic interaction; theoretical understanding.